Landscape Design of Rural Rainwater Utilization Based on LID Concept. Issue 1 (November 2020) - Gui, Yu; Zhang, Ruixuan
Abstract: This article takes farmland, roads, and rural residential areas as the starting point for effective rainwater planning and utilization. It is useful to purifies and reuses rural water sources, and promotes the improvement of rural ecosystems. Rural rainwater resources are lost and pollution is serious. The design of Low Impact Developmentrainwater use in rural landscape has become the focus of this article. This article mainly combines the rural terrain and environment, optimizes rainwater ecology, combines the use of storage gutters to form an ecological water cycle, builds rooftop gardens in rural residential areas, transforms landscape ecological vegetable gardens, and transforms permeable courtyards, and conducts landscape design. Through the ingenious combination of technology and art, landscape design such as rural rainwater collection, runoff mitigation, purification and infiltration, and agricultural applications is realized to meet the needs of household water and green irrigation, while improving the environmental quality of rural landscapes. By adopting the Low Impact Development rainwater landscape design, it highlights the sustainable development of rural landscape ecology.